Assessment of Live Lactobacilli Recovery from Probiotic Products for Vaginal Application - Diana Neves Sousa; Carlos Gaspar; Joana Rolo; Gilbert G. G. Donders; José Martinez-de-Oliveira; Rita Palmeira-de-Oliveira; Ana Palmeira-de-Oliveira (Applied Microbiology, 2023)
The interest in the use of probiotics to treat and prevent vaginal infections is known. The new regulation of medical devices by the European Medical Agency (EMA) introduced big changes in Europe regarding probiotic products for vaginal application, as they are no longer considered as medical devices. As the future classification will be as drugs, it will stress the need to define robust and reliable pre-clinical in vitro testing in order to assess the quality, safety and efficacy of probiotics for human use. Before discussing the efficacy in human pathology, it is mandatory to evaluate the survival and multiplication potential of probiotic strains when brought into contact with vaginal fluid. In this work, our objective was to assess the recovery and stability profile of lactobacilli from six vaginal probiotic formulations brought in contact with specific culture media or vaginal fluid simulants (VFS). Overall, the recovery of viable lactobacilli cells from a modified vaginal fluid simulant (MVFS) solution was comparable to the recovery pattern obtained in standard culture medium. Therefore, we conclude that the MVFS seems to better simulate the conditions of the human vaginal fluid, in contrast with other simulants, and may be used to predict the viability of probiotics over time in the normal vaginal milieu. We discovered that each probiotic product has a unique profile that requires stand-alone studies in conditions that mimic the in vivo status in order to assess their preclinical effectiveness and promote their differential use by the medical community.